Chicken Soup for the Soul : Think, Act &? Be Happy : How to Use Chicken Soup for the Soul stories to Train Your Brain to Be Your Own Therapist - Newmark, Amy
Book combines true, personal Chicken Soup for the Soul stories with advice from New York Times bestselling psychoanalyst Dr. Mike Dow, who shows readers how to use the lessons in the stories to practice Cognitive Behavioral Therapy on themselves - how